MicroRNA‐497 inhibits invasion and metastasis of colorectal cancer cells by targeting vascular endothelial growth factor‐A. (3rd February 2016) - Qiu, Yanyan; Yu, Hui; Shi, Xiaojing; Xu, Ke; Tang, Qingfeng; Liang, Bo; Hu, Songjiao; Bao, Yijie; Xu, Jianhua; Cai, Jie; Peng, Wen; Cao, Qin; et al.
Abstract: Objectives: microRNAs (miRNAs), are non‐coding RNAs that regulate gene expression, and are involved in tumour development. The aim of this study was to investigate microRNA‐497 (miR‐497) expression and its role in development of colorectal cancer (CRC). Materials and methods: RT‐PCR was performed to detect expression of miR‐497 in CRC cell lines (HCT8, LOVO, Ls‐174, HCT116 and HT29) and in clinical cancer specimens. To further understand its role, we restored expression of miR‐497 in the HCT116 cell line by transfection with miR‐497 mimics or inhibitors. Effects of miR‐497 on cell proliferation, migration and invasion of targets were also determined both in vitro and in vivo . Results: miR‐497 expression decreased in 34 CRC tissues compared to non‐tumour tissues and in tumour cell lines. Overexpression of miR‐497 did not inhibit cancer cell growth but suppressed metastasis and invasion both in vitro and in vivo . Vascular endothelial growth factor‐A (VEGF‐A) was confirmed to be a target of miR‐497. Furthermore, we found overexpression of miR‐497 altered expression of key molecules of the VEGF‐A/ERK/MMP‐9 signalling pathway. Conclusions: Thus our results provide evidence that miR‐497 might function as a metastasis suppressor in CRC. Targeting miR‐497 may provide a strategy for blocking its metastasis.